1964
DOI: 10.1042/bj0910620
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of glucose 1-phosphate and glucose 6-phosphate and their influence on the metabolism of glucose in rat-diaphragm muscle

Abstract: In a previous investigation carried out in this Laboratory (Beloff-Chain et al. 1953) it was found that isolated rat diaphragm synthesized glycogen from glucose and from glucose 1 -phosphate to about the same extent when the substrate concentration, calculated as glucose, was 2 %. There was little or no glycogen synthesis from glucose 6-phosphate at this concentration. Further, it was shown that insulin had no stimulatory effect on glycogen synthesis from glucose 1-phosphate as it had from glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1966
1966
1991
1991

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Lactate. Loss of lactate by evaporation from the 1973 chromatography paperwas decreased by exposing the papers to NH3 fumes (Bradford et al, 1969) and performing the radioautography at -20°C (Beloff-Chain et al, 1955).…”
Section: Methodsmentioning
confidence: 99%
“…Lactate. Loss of lactate by evaporation from the 1973 chromatography paperwas decreased by exposing the papers to NH3 fumes (Bradford et al, 1969) and performing the radioautography at -20°C (Beloff-Chain et al, 1955).…”
Section: Methodsmentioning
confidence: 99%
“…[U-14C]Glucose, [U-14C] Incubation of rat brain tisue. The conditions of incubation were the same as those described by Beloff- Chain et al (1955a) and Beloff-Chain, Catanzaro, Chain, Masi & Pocchiari (1955b.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of samples for tissue-radioactivity measurements. The methods of preparation of tissue extracts after incubation and the methods of chromatography were those described by Beloff-Chain et al (1955a. The braincortex slices were removed from the Warburg vessels, blotted on filter paper and rapidly washed in three lots of Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…(Nigam, 1967a) and in isolated rat diaphragm (Beloff-Chain et al 1964;Landau & Sims, 1967), glucose 6-phosphate is a poorer precursor of glycogen than glucose, although its catabolism to carbon dioxide or lactate or both exceeds that of glucose. Glucose 6-phosphate also activates glycogen synthesis from [14C]glucose in rat diaphragm (Beloff-Chain et al 1964) and in tumour cells (Nigam, 1967a) despite its being an inhibitor of mammalian hexokinase (Crane, 1962) and a diluent of label in glucose 6-phosphate formed from [14C]glucose. In other studies the rate of glycogen synthesis in the starved diabetic rat has been shown to be higher than the activity of hexokinase in the supernatant fraction of liver of these rats (Friedmann, Goodman & Weinhouse, 1967).…”
mentioning
confidence: 99%